Evaluación de diferentes tácticas para el control de gasterópodos (babosas terrestres) en el cultivo de lechuga (lactuca sativa l. Var. Fallgreen) en la zona de el guarco de Cartago - Salazar-Rojas, Kevin Arturo; Granados-Muñoz, José Andrés (Instituto Tecnológico de Costa Rica, 2014)
The terrestrial slugs are responsible for causing considerable economic losses on agricultural crops, some countries such as England, Thailand, United States, Colombia, Nicaragua, among others, report strong impacts on diverse crops. Nevertheless, its importance extends not only in these millionaire losses, but also for they act as intermediate vectors of the Angiostrongylus costaricensis nematodes, causing intestinal damages in the human being. Regarding to the previous information, it has promoted different investigations in the last years, with the aim of establishing efficient management tactics that allow to keep the populations below the economic threshold of damage. Within these tactics, they are synthetic substances as the metaldehyde and carbamates which are applied in different concentrations, shaped like pellets, same that by its characteristics in the short or medium term can have a repercussion on the biodiversity, so as an alternative to this tactic, the use of different types of traps around and within the plantations have generated reliable results. On the other hand, the use of botanical extracts of plant origin act on the behavior of this pest causing ,not only a repellent effect , but also a inedible reaction, so linked to the above, the use of agents of biological control such as the Phasmarhabditis hermaphrodita nematode, entomopathogenic microorganisms such as Pochonia chlamydosporia, and predators such as Scarites anthracinus y Pterostichus melanarius, have demonstrated a positive impact, not only in the management of terrestrial slugs, but also in the general equilibrium of the present populations in the crop, giving long-term benefits.
Tesis (Licenciatura en Ingeniería en Agronomía). Instituto Tecnológico de Costa Rica, Escuela de Agronomía,2014
Keywords: Uso del suelo; Agricultura; Plagas agrícolas; Cultivos agrícolas; Plagas agrícolas